2010
DOI: 10.1007/s00122-009-1253-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping candidate QTLs related to plant persistency in red clover

Abstract: Red clover (Trifolium pratense L.) is a diploid (2n = 14), self-incompatible legume that is widely cultivated as a forage legume in cold geographical regions. Because it is a short-lived perennial species, improvement of plant persistency is the most important objective for red clover breeding. To develop a marker-assisted selection (MAS) approach for red clover, we identified candidate QTLs related to plant persistency. Two full-sib mapping populations, 272 × WF1680 and HR × R130, were used for QTL identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Genetic analyses including QTL discovery have contributed to understanding of the trait, with QTL for stem length, seed yield and persistence all co-located (Herrmann et al, 2008). An independent study identified QTL for plant persistence on groups 3 and 6 (Klimenko et al, 2010). Narrowsense heritability estimates for forage yield traits ranged from moderate to low (Taylor and Smith, 1979).…”
Section: Downloaded By [West Virginia University] At 06:45 20 Novembementioning
confidence: 98%
See 1 more Smart Citation
“…Genetic analyses including QTL discovery have contributed to understanding of the trait, with QTL for stem length, seed yield and persistence all co-located (Herrmann et al, 2008). An independent study identified QTL for plant persistence on groups 3 and 6 (Klimenko et al, 2010). Narrowsense heritability estimates for forage yield traits ranged from moderate to low (Taylor and Smith, 1979).…”
Section: Downloaded By [West Virginia University] At 06:45 20 Novembementioning
confidence: 98%
“…Cold tolerance contributes to red clover yield and persistence in northern latitudes (Klimenko et al, 2010;Ravagnani et al, 2012), but its basis and genetic variation have been less investigated than in alfalfa and white clover. Red clover is not considered reliably persistent in cold-winter conditions.…”
Section: Cold Tolerancementioning
confidence: 99%
“…Klimenko et al (2010) developed a marker-assisted selection approach for red clover to identify candidate QTLs related to plant persistency. This is a complex trait and its investigation was associated with resistance to biotic stress caused by the most frequent pathogens Sclerotinia trifoliorum and Fusarium species (F. oxysporum, F. solani, and F. roseum), as well as to abiotic stress connected with low temperature (winter hardiness).…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…Herrmann et al [43] used vigour scores after three growing seasons to identify QTL for persistence on LG3. Klimenko et al [44] used two of the mapping families described above [42] to identify QTL for winter hardiness, resistance to S. trifoliorum and the root rot fungus Fusarium, and found consistent QTL on linkage groups 1, 3 and 6. Given the complex nature of these traits, it is not surprising that the heritabilities they reported were quite low.…”
Section: Genetics and Breedingmentioning
confidence: 99%
“…Given the complex nature of these traits, it is not surprising that the heritabilities they reported were quite low. It was also noticeable that a range of interacting QTLs were identified, highlighting the fact that pyramiding single effect QTLs may not bring sufficient improvement to breeding populations, but that it is important to ensure that all the interacting QTLs are present in the elite germplasm [44].…”
Section: Genetics and Breedingmentioning
confidence: 99%